2005
DOI: 10.1098/rsbl.2005.0339
|View full text |Cite
|
Sign up to set email alerts
|

Costly parasite resistance: a genotype-dependent handicap in sand lizards?

Abstract: Male sand lizards (Lacerta agilis) with a specific restriction fragment length polymorphism fragment in their major histocompatibility complex (MHC) genotype ('O-males') are more resistant to ectoparasites (a tick, Ixodes ricinus) than are males that lack this fragment ('NO-males'). However, emerging evidence suggests that such adaptive immune responses are costly, here manifested by reduced body condition and a compromised defence against secondary infections by haemoprotid parasites that use the ticks as vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…Numerous studies have demonstrated endoand ectoparasites being costly for the host (Klukowski & Nelson, 2001;Bouma et al, 2007). Ticks have been demonstrated to act as vectors of lizard blood parasites, Haemolivia stellate (Haemogregarinidae) (Lainson, De Souza & Franco, 2007) and to decrease their hosts' body condition (Dunlap, 1993), while parasite resistance was also shown to be costly (Olsson et al, 2005) and in trade-off with male reproductive success (Uller & Olsson, 2003). Thus, an individual with the ability to avoid such detrimental effects is possibly of better quality.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated endoand ectoparasites being costly for the host (Klukowski & Nelson, 2001;Bouma et al, 2007). Ticks have been demonstrated to act as vectors of lizard blood parasites, Haemolivia stellate (Haemogregarinidae) (Lainson, De Souza & Franco, 2007) and to decrease their hosts' body condition (Dunlap, 1993), while parasite resistance was also shown to be costly (Olsson et al, 2005) and in trade-off with male reproductive success (Uller & Olsson, 2003). Thus, an individual with the ability to avoid such detrimental effects is possibly of better quality.…”
Section: Discussionmentioning
confidence: 99%
“…We do not deal with studies on preference for specific alleles (e.g. Olsson et al 2005) because those data are not compatible with the standard technique based on meta-analytic means. Our goals in this study were threefold.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Pincheira-Danoso (2013), a Classe Reptilia possui 82 famílias, 1131 gêneros e 9546 espécies. Essa é subdividida em Ordem Squamata, a qual agrupa serpentes, lagartos e anfisbaenias; Ordem Crocodylia, jacarés, gaviais e crocodilos; Ordem Testudinata, cágados, tartarugas e jabutis e a Ordem Rincocephalia, que possui uma única família, gênero e espécie, a tuatara.…”
Section: Répteisunclassified
“…No presente estudo, os primers amplificaram, com sucesso, o DNA de hemogregarinas em répteis, sendo possível identificar gêneros e espécies. A eficiência desses primers e dessa regição gênica vem sendo descrita na literatura por diversos autores, como ODwyer et al (2013). Os pesquisadores compararam os primers que amplificam o gene 18S e primers que amplificam outros genes (como o ITS-1, 5.8S e ITS-2), todos da região ribossomal, com a finalidade de identificar e caracterizar as espécies de Hepatozoon em serpentes e os resultados obtidos apontaram os pares de oligonucleotídeos HepF300/Hep900 e HEMO1/HEMO2 como eficientes.…”
Section: Análise Molecularunclassified
See 1 more Smart Citation